2020
DOI: 10.1200/jco.19.03205
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter International Society for Immunotherapy of Cancer Study of the Consensus Immunoscore for the Prediction of Survival and Response to Chemotherapy in Stage III Colon Cancer

Abstract: PURPOSE The purpose of this study was to evaluate the prognostic value of Immunoscore in patients with stage III colon cancer (CC) and to analyze its association with the effect of chemotherapy on time to recurrence (TTR). METHODS An international study led by the Society for Immunotherapy of Cancer evaluated the predefined consensus Immunoscore in 763 patients with American Joint Committee on Cancer/Union for International Cancer Control TNM stage III CC from cohort 1 (Canada/United States) and cohort 2 (Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 45 publications
12
124
3
Order By: Relevance
“…Stage I to III CRC with high Immunoscore has been shown to be associated with lower recurrence risk than tumours with low Immunoscore (HR, 0.20; p < 0.0001) [ 97 ]. More specifically for patients with stage III disease, a recent retrospective series including patients untreated and those treated with a variety of adjuvant chemotherapy regimens reported 3-year recurrence-free rates of 56.9% and 76.4% in patients with low and high Immunoscores, respectively (HR, 0.48; p < 0.0003) [ 98 ]. A separate analysis in the high-risk stage II (T4N0) subset demonstrated a 5-year recurrence rate of 84.6% in patients with intermediate/high Immunoscore and 46.3% in patients with low Immunoscore [ 99 ].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Stage I to III CRC with high Immunoscore has been shown to be associated with lower recurrence risk than tumours with low Immunoscore (HR, 0.20; p < 0.0001) [ 97 ]. More specifically for patients with stage III disease, a recent retrospective series including patients untreated and those treated with a variety of adjuvant chemotherapy regimens reported 3-year recurrence-free rates of 56.9% and 76.4% in patients with low and high Immunoscores, respectively (HR, 0.48; p < 0.0003) [ 98 ]. A separate analysis in the high-risk stage II (T4N0) subset demonstrated a 5-year recurrence rate of 84.6% in patients with intermediate/high Immunoscore and 46.3% in patients with low Immunoscore [ 99 ].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Namely, patients showing high GrB + lymphocytes and MSI phenotype were those showing the more favorable relapse-free rates [ 27 ]. Other researches [ 54 ] pointed to the association of high load of TILs (assessed as intraepithelial CD8 + cells) with better long-term outcome of colon cancer patients. Furthermore, in light of the temporal pattern of the reduced risk associated with high CD8 + TILs (that became significant only after 2 years), they hypothesized an immune surveillance towards micro-metastases strongly correlated with the local amount of CD8 + cells.…”
Section: The Journey Of Adaptive Immune Response To Colon Cancer Fmentioning
confidence: 99%
“…[11][12][13][14] Indeed, the international Immunoscore consortium recently demonstrated that Immunoscore predicted survival and response to chemotherapy in 763 Stage III colon cancer (CC) patients. 15 The prognostic value of Immunoscore was confirmed in two independent phase 3 clinical trials (NCCTG-N0147, n = 559; Prodige-IDEA, n = 1062). 16,17 Moreover, results from IDEA phase 3 randomized trial revealed the predictive value of Immunoscore for response to adjuvant FOLFOX chemotherapy duration.…”
Section: Resultsmentioning
confidence: 93%